YATHĀBHŪTAÑĀṆADASSANAṂ: A STUDY OF KNOWLEDGE & VISION OF THINGS AS THEY ARE - Hai Yen, Nguyen (International Journal For Research In Educational Studies, 2023)
Based on the basic teachings of Buddhism in the Sutta Pitaka, this article is written to clarify the meaning of Yathābhūtañāṇadassana (seeing things as they are) in the Theravada Buddhist tradition. Through research, the writer wishes the reader to gradually become aware of the real nature of the world as ever-changing, unstable, and ephemeral. Moreover, by understanding the true nature of all things, each person knows how to live peacefully in the present moment as well as has one's capacity to face the disadvantages of daily life with a peaceful mind.